2020
DOI: 10.4038/tare.v23i1-2.5495
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of genetic variability parameters for <em>Septoria tritici</em> blotch resistance and quantitative traits in bread wheat genotypes

Abstract: Septoria tritici Blotch (STB) is one of the most devastating diseases of wheat in Ethiopia and worldwide. The present study was conducted to assess the genetic variability of yield and yield parameters among different bread wheat genotypes grown under the stress of Septoria tritici Blotch. A total of 180 bread wheat lines, advanced genotypes and released varieties were included in the investigation. Genetic variance, heritability, correlation and ANOVA were estimated for S.tritici, and yield and yield paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…High and moderate heritability values for disease severity parameters, such as SDSM and SPC, indicate that STB resistance genes are less influenced by the environment. The current result is in agreement with the results of Gerema et al (2020), who reported moderate heritability values for septoria disease resistance.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…High and moderate heritability values for disease severity parameters, such as SDSM and SPC, indicate that STB resistance genes are less influenced by the environment. The current result is in agreement with the results of Gerema et al (2020), who reported moderate heritability values for septoria disease resistance.…”
Section: Resultssupporting
confidence: 94%
“…Analysis of variance (ANOVA) revealed highly significant variation ( P < .001) between genotypes (G), environment (E), and G × E interaction regarding response to septoria disease severity at heading (SDSH), septoria disease severity at maturity (SDSM), septoria progress coefficient (SPC), days to heading (DH), plant height (PH), and spike length (SL) (Table 1). Similarly, Gerema et al (2020) also reported that the mean squares of septoria disease severity and phenological traits exhibit a great deal of genetic diversity in Ethiopia.…”
Section: Resultsmentioning
confidence: 88%